Anticonnective tissue and other antitissue 'antibodies' in the sera of patients with coeliac disease compared with the findings in a mixed hospital population. Issue 6 (June 1976) - Williamson, N; Asquith, P; Stokes, L; Jowett, W; Cooke, W T
Abstract : Serum IgG specificities directed against various components of basement membrane and reticulin have been described, and their incidence in 138 patients with coeliac disease has been compared with that in 110 hospital inpatients, 100 normal blood donors, and 1441 other patients. A wide variety of antitissue specificities were observed but only a few appeared to be of any significance. The 'antireticulin' specificities have been subdivided into different groups according to their distinctive histological staining patterns. Specificity directed primarily against endothelial basement membrane was found most frequently in the sera of patients with hiatus hernia (35%) or coeliac disease (22%). The same specificity was also observed in patients with myasthenia gravis and to a lesser extent in Crohn's disease and in a mixed group of patients with unspecified organic gastrointestinal disease. An epithelial basement membrane reactivity was found in patients with rheumatoid arthritis but only rarely in other conditions. Staining of perivascular connective tissue represented a third type of 'antireticulin' specificity. It was found only rarely, although in coeliac disease this reactivity was found more frequently in combination with other connective tissue specificities.